Moral Responsibility and Self-Regulation in Character Education: Evidence from Draz's Quranic Ethics - Didi Darmadi; Muhammad Kholid Muslih; Zahratur Rofiqah Binte Mochamad Sandisi; Desnas Artanti (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study examines the relationship between moral responsibility and self-regulation in character education based on Muhammad Abdullah Draz’s ethical framework, employing a mixed-methods design. Draz’s ethical theory consists of several interrelated concepts, namely al-ilzâm (moral obligation), al-masûlîyah (moral responsibility), al-nîyah (intention), al-juhd (moral striving), and al-jazâ (moral consequence). Among these concepts, the present study specifically focuses on al-masûlîyah (moral responsibility) in relation to students’ self-regulation within the context of character education. The quantitative phase involved students in several schools, where data were collected using structured questionnaires and analyzed through correlation and regression analysis. The qualitative phase involved interviews to explore how moral responsibility is internalized and expressed in students’ daily behavior. The quantitative findings indicate that moral responsibility has a significant positive effect on students’ self-regulation. It suggests that higher levels of moral responsibility are associated with stronger self-regulatory capacities in learning and behavior. Supporting the result, the qualitative findings show that moral responsibility is developed through processes of reflection, habituation, and moral awareness within both classroom and school environments. Overall, the principles of al-masûlîyah (moral responsibility) and al-ilzâm (moral obligation) provide a robust conceptual framework for understanding character development, particularly in explaining how moral values shape students’ self-regulated behavior in the educational context of schools. Thus, Draz’s theory makes a significant contribution to the development of holistic, value-based character curricula and pedagogy that are responsive to contemporary social change.